Neutropenic Diet Cannot Reduce the Risk of Infection and Mortality in Oncology Patients With Neutropenia - Yimei Ma; Yimei Ma; Xiaoxi Lu; Xiaoxi Lu; Hanmin Liu; Hanmin Liu; Hanmin Liu; Hanmin Liu; Hanmin Liu (Frontiers in Oncology, 2022)
BackgroundThe purpose of this systematic review and meta-analysis was to evaluate the effect of a neutropenic diet and a control diet on infection and mortality rates in oncology patients with neutropenia.MethodsWe searched the following English electronic databases: PubMed, Embase, Cochrane Central Register of Controlled Trials, and Google Scholar Engine. Published studies involving neutropenic diets (study group) and control diets (control group) in oncology patients with neutropenia were searched. The focus of the meta-analysis was on the outcomes of infection and mortality rates. A subgroup analysis was also performed.ResultsA total of 6 studies were included, with a total sample size of 1114 patients. The patients in the study group had a similar infection rate compared with the patients in the control group (P = 0.11). The patients in the study group had a similar mortality rate compared with the patients in the control group (P = 0.74). Another subgroup analysis showed that the incidence of infection was also similar for pediatric (P = 0.74) and adult (P = 0.11) oncology patients between the study and control groups.ConclusionsBased on the current evidence, this meta-analysis showed that the application of a neutropenic diet cannot reduce the risk of infection and mortality in oncology patients with neutropenia. However, more rigorous randomized controlled trials are needed to confirm this conclusion in the future.